From Latent Grievances to Collective Action: A Qualitative Case Study of Residents’ Rejection of the Ummi Cinta Majelis Taklim in Bekasi - Fitriah elkarimah, Mia; Susilawati, Susilawati; Fuadah, Siti (Tasyri' : Journal of Islamic Law, 2026)
This article examines a local socio-religious conflict involving residents’ collective action against the Ummi Cinta Majelis Taklim (Al-Kautsar) in the Dukuh Zamrud Housing Complex, Bekasi City. The conflict reflects a broader pattern in Indonesia, where religious disputes often emerge from social, spatial, and procedural tensions rather than doctrinal differences. This study aims to explain how residents’ grievances developed into collective action, how objections were expressed through RT/RW neighborhood structures, how formal reporting mechanisms involved the Indonesian Ulema Council (MUI) and local government, and why residents prioritized official channels over informal pressure. Using a qualitative instrumental case study design, the research employs semi-structured interviews, observation, and document analysis, and analyzes data through the Miles and Huberman interactive model with triangulation. The findings indicate that grievances accumulated for nearly eight years due to exclusive activities, increasing numbers of external congregants, and recurring disturbances to traffic, noise, and spatial comfort, which were later intensified by viral allegations of doctrinal deviation. Collective action initially appeared in symbolic forms such as protest banners and later became institutionalized through RT/RW reporting and coordinated engagement with authorities and MUI. MUI’s clarification shifted the conflict from doctrinal to socio-procedural issues, enabling administrative resolution through activity restrictions, permit requirements, and relocation. This study concludes that the conflict is best understood as a governance problem of non-formal religious spaces and highlights the importance of dialogical and evidence-based approaches in managing socio-religious disputes.